IMPLEMENTATION OF 5S HOUSEKEEPING MANAGEMENT SYSTEM IN THE FILE BANK ROOM BRI KCP UNIT CIMANUK GARUT - Ahadi, Ikhsan; Fauzan, Fadhil Hafidz; D, M. Farhan Algifari; Amaluna, Muhammad Iqbal; Na’Vio, Tunjang Ade; Rahmana, Arief (CENTRAL ASIA AND THE CAUCASUS, 2022)
BRI KCP Unit Cimanuk Garut office serves thousands of customers so that every day there are many documents in and out of the branch office. Branch offices allow financial institutions such as banks to expand services to areas beyond the location of the headquarters. Opening a branch office can be a non-costing approach because not all bank office locations are required to offer the same level of service as the head office. The guarantee documents submitted by customers of Bank BRI Unit Cimanuk Garut are stored in the file room to maintain the security of documents and avoid damage and make it easier for employees to check the customer's documents. The goal of the study was the implementation of the 5S method in the hope of avoiding waste and prioritizing the positive behavior of every worker in the file room in order to create a comfortable work environment. The research method used is the 5S method, while the data collection technique uses a qualitative approach by making observations. PDCA is used as a tool to improve the 5S implementation process in the file room of Bank BRI KCP Unit Cimanuk Garut. The condition of the room becomes comfortable and makes it easier for workers when archiving files because the room is more organized. The addition of tables and chairs is expected to improve posture, reduce fatigue, give a sense of comfort and reduce motion waste in doing work. Cleaning activities are carried out so that the room becomes clean, neat and comfortable. The provision of 5S displays in the room is intended so that the 5S culture is always maintained. A good and comfortable work culture will make the company successful and advanced because it affects the psychological condition of the workers who perform their responsibilities and work in the company.